A two-item screening of maternal or infant perceived life threat during childbirth prospectively associated with childbirth-related posttraumatic stress symptoms up to six months postpartum: two observational longitudinal studies - Gilbert, Leah; Sandoz, Vania; Deforges, Camille; Horsch, Antje (Frontiers in Psychiatry, 2024)
This study investigated prospective relationships between the perception of threat to one's own life or to that of one's infant during childbirth and maternal childbirth-related posttraumatic stress symptoms (CB-PTSS) and probable childbirth-related posttraumatic stress disorder (CB-PTSD) in a community and ECS sample.Study samples included 72 mothers from a community sample and 75 mothers after emergency cesarean section.Perceived maternal and infant life threat were assessed at ≤1 week postpartum. Maternal CB-PTSS and probable CB-PTSD were assessed with validated questionnaires up to 6 months postpartum. Covariates were extracted from hospital records. Secondary data analysis with logistic and linear regressions was performed.Globally, mothers were significantly more likely to perceive their infant's life to be threatened, rather than their own. Both types of perceived threat were prospectively but differentially associated with maternal CB-PTSS and probable CB-PTSD at 4-6 weeks and 6 months postpartum. Statistical significance was set at p<0.05.The type of perceived threat differently influences maternal CB-PTSS and probable CB-PTSD up to 6 months postpartum. These results may be the basis for the development of a short screening instrument after traumatic childbirth in clinical settings. Future studies need to assess the psychometric properties and acceptability of such a brief screening tool.